HUBUNGAN KETERAMPILAN GURU DALAM MENGAJAR DENGAN MOTIVASI BELAJAR SISWA KELAS VIII SMP KALAM KUDUS MEDAN - Sinarsi Meliala; Laksana Tobing (JURNAL PSYCHOMUTIARA, 2022)
This research is conducted considering the number of students of grade VIII SMP Kalam Kudus Medan has value below the value of Minimum Criterion Criteria (KKM), which is caused by lack of motivation in learning because of the lack of teaching skills. This study aims to find the relationship of teachers' skills in teaching with the motivation to learn the students of grade VIII SMP Kalam Kudus Medan. The population in this study are students of grade VIII SMP Kalam Kudus Medan with the number of 70 people. The type of sample used is total sampling. Data collection techniques using indirect communication techniques, namely by spreading the questionnaire. Data analysis techniques using statistical analysis. The statistical test used is Product Moment correlation test. The results showed that the correlation value rxy = 0.702. Relationship rxy = 0.702 based on correlation coefficient analysis indicates that the relationship includes a strong relationship. Hypothesis test results of correlation value rxy = 0.702 is said to apply in general, then Ho is rejected and Ha accepted. This means that there is a relationship of teacher skills in teaching with the motivation to learn the students of grade VIII SMP Kalam Kudus Medan.